2018
DOI: 10.1177/0967010617730975
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the colonial: The (re)production of ‘African’ exceptionalism in critical security and military studies

Abstract: Drawing on postcolonial theory, this article queries into the ways in which the concepts of militarism/militarization and securitization are applied to ‘African’ contexts. We highlight the selective nature of such application and probe into the potential reasons for and effects of this selectiveness, focusing on its signifying work. As we argue, the current selective uses of securitization and militarism/militarization in ‘Africa’ scholarship tend to recreate troublesome distinctions between ‘developed’ versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Yet, while North-South inequalities in knowledge production are indeed strong, particularly in relation to research on Africa (Boshoff 2009, Mwambari andOwor 2019), much conflict research is also conducted by researchers based in, or originating from, the global South (D'Costa 2011, Parashar 2014; see also Henry 2003) who also make use of brokers in their research. In short, imagining the researcher-broker relationship simply as reflecting a North/ South divide problematically downplays the research conducted by scholars from 'the Global South', in turn reflecting the problematic trend of Northern white navel-gazing marking much of post-colonial studies (Chakrabarty 2000, Eriksson Baaz andVerweijen 2018). As highlighted particularly in the contributions by Alfred Banga et al, Parashar and Myrttinen and Mastonshoeva conducting research in 'native areas' (see Parashar) pose particular dilemmas and challenges.…”
Section: Brokers?mentioning
confidence: 99%
“…Yet, while North-South inequalities in knowledge production are indeed strong, particularly in relation to research on Africa (Boshoff 2009, Mwambari andOwor 2019), much conflict research is also conducted by researchers based in, or originating from, the global South (D'Costa 2011, Parashar 2014; see also Henry 2003) who also make use of brokers in their research. In short, imagining the researcher-broker relationship simply as reflecting a North/ South divide problematically downplays the research conducted by scholars from 'the Global South', in turn reflecting the problematic trend of Northern white navel-gazing marking much of post-colonial studies (Chakrabarty 2000, Eriksson Baaz andVerweijen 2018). As highlighted particularly in the contributions by Alfred Banga et al, Parashar and Myrttinen and Mastonshoeva conducting research in 'native areas' (see Parashar) pose particular dilemmas and challenges.…”
Section: Brokers?mentioning
confidence: 99%
“…Militarism and militarization have been interpreted and conceptualized in a number of different ways, and the most refined approaches have been produced for countries of the global North (Enloe, 2016; Mann, 1987; Shaw, 2013; Stavrianakis and Selby, 2013). Although such approaches may not correspond closely to the realities of the global South (Eriksson-Baaz and Verweijen, this issue), it is possible to tailor the concepts to the situation in such countries. Stavrianakis and Selby point out that empirical studies have shown that ‘militarism is characteristic of global North and global South alike’ – indeed, ‘[the concept] is of global relevance and applicability’ (Stavrianakis and Selby, 2013: 3, 11).…”
Section: A Conceptual Toolbox For the Colombian Casementioning
confidence: 99%
“…Militarism in postcolonial nation-states is often attributed to the lack of Western notions of professionalism and discipline in the armed forces that enables the latter to permeate easily into civilian lives and values (Luckham, 1994; cf. Eriksson Baaz and Verweijen, this issue). However, as the case of India demonstrates, ‘postcolonial anxiety’ does not result in uniform adherence to or a linear trajectory of militarism in postcolonial states.…”
Section: Introductionmentioning
confidence: 99%